Molecular modelling of polypropylene crystallization - Ahmad Azmi, Aini Shafinaz (2017)
Polypropylene is a semicrystalline polymer where crystallinity is usually in the range 40-70% and it also depends on the level of tacticity of the polymer. Different crystal modifications can exist depending on the condition of the crystallization process and isotacticity of polypropylene. These changes also create differences in strength, heat resistance and pressure bonding properties. Materials Studio software package is used for the simulation of polypropylene. The molecular simulation is carried out using the forcite module, using the Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies (COMPASS) force field. The limitation of this research was only isotactic polypropylene was investigated in this paper. In conclusion, the growth of spherulite or the crystallization of polypropylene can be affected by the cooling rates, temperature, tacticity and many more. However as for isotactic propylene, a few types of spherulites can be formed based on the condition of the crystallization process. The molecular model of polypropylene at 333K was simulated as in figure 4.2, where it starts to crystallize. Figure 4.3, it can be concluded that it has the total energy of -4.960 kcal/mol. At temperature 435 K where it exists as melt, and it is hard to crystallize, the chain conformation of isotactic propylene exists with the configuration of right-up helices. The helix conformation leads to the lowest interaction energy between the methyl groups. From figure 4.5, it can be concluded that it has the total energy of 11.245 kcal/mol.